Technology-enhanced project-based learning in a large undergraduate Anthropology lecture course - Ahmadi, Zia (Kansas State University, 2011)
The goal of this exploratory case study was to answer two questions: 1. How does an exemplary on-campus undergraduate large Introduction to Cultural Anthropology course encompass the PBL learning model characteristics, specifically focusing on the following: 1.1) Driving question, 1.2) Student construction of an artifact, 1.3) Teachers’ role, and 1.4) Assessment? 2. How is technology used by the professor, teacher assistants, and students to support project-based learning? To answer these questions, the researcher studied a large Introduction to Cultural Anthropology class, which consisted of the professor, ten teaching assistants (TAs), and 400 students. The students were divided into 20 recitation sections, with 20 students in each section. Each TA was assigned two recitation sections. Observations were conducted on twice-weekly Professor’s lectures and three once-weekly recitation sessions. Additionally, interviews and follow-up interviews were conducted of the professor, three teaching assistants (TA), and nine students. Finally, documents analyzed included the professor’s course materials and course management documents. With respect to Research Question 1, “How does an exemplary on-campus undergraduate large Introduction to Cultural Anthropology course encompass the PBL learning model characteristics, specifically focusing on the following: 1.1) Driving question, 1.2) Student construction of an artifact, 1.3) Teachers’ role, and 1.4) Assessment?”, research findings indicated that all four elements of the PBL model were present in this class and were executed well. Research Question 2, “How is technology used to support PBL,” findings indicated that advanced technologies were used by the professor for course purposes. These technologies included Wetpaint (the wiki course management system) and Facebook. More conventional technologies, such as e-mail, were also used for this purpose. Though students were hesitant to use course technology in the beginning. However, with the help of the professor and TA’s, the students learned to use the course technology and grew to enjoy it. Two additional themes emerged through open coding: Emotional Involvement and Non-Participation. First, the TA’s and students developed emotional ties to the cultures that they created in their recitation sections. Second, some students did not participate in either the lecture or the recitation sessions. The TAs took non-participation seriously, both in terms of class participation, individually, and in terms of student responsibilities to the group recitation session in culture construction.
Keywords: Constructivism; Technology-enhanced Project-based learning; Project-based learning; Social Media; World Simulation; Real-world experience; Education, General (0515); Education, Technology (0710)